Religious Pilgrimages in the Mediterranean World - Pazos, Antón M. (Taylor & Francis Group, 2023)
Examining the evolution of recent theoretical and methodological trends in pilgrimage studies and featuring essays from leading scholars in various fields in the humanities, this book is an essential read for all researchers of pilgrimage, religious history, religious tourism, and anthropology.